Unveiling the Dynamic Landscape: Exploring Practices, Challenges, and Resilience Strategies of Digital Leaders in Secondary Education - Danganan, Catherine G.; Gamboa, Alberto G. (Journal of Cultural Analysis and Social Change, 2025)
Education institutions are increasingly affected by rapid technological advancement which drives school leaders to foster the culture of innovation and do digital transformation. Guided by change management theory, this qualitative exploratory study investigates the practices, challenges and resilience strategies of seven (7) secondary school digital leaders. Data were collected using semi-structured interviews and analyzed using reflexive thematic analysis. The findings highlight on their leadership practices such as capacity building and professional development, instructional supervision and monitoring, strategic technology integration and, advocacy and digital leadership mindset, while also revealing the persistent challenges including infrastructures and resource constraints, resistance to technological change, and professional development needs. Importantly, study also uncovers the resilience strategies used by these school leaders, such as adaptation through continuous learning, resilience in managing challenges, collaboration and support networks, strategic, stress management and proactive leadership and innovation. The findings are grounded on the change management theory, as it provides a framework for understanding how digital leaders incorporate, integrate and implement technological innovations in their respective schools. Based from the findings, the study recommends a comprehensive technology-oriented professional development policy measures that address infrastructure gaps, build change readiness, and enhance leader collaboration in the organization. These findings offer actionable insights for strengthening digital leadership capacity and sustaining technology-driven educational reform.